Exposure to maternal methadone in utero: visual and developmental outcomes at 6 months. (4th April 2011) - McGlone, L; Hamilton, R; McCulloch, D L; MacKinnon, J; Bradnam, M S; Groundland, A; McIntosh, M; Weaver, L T; Mactier, H
Abstract : Aims: There is increasing evidence that maternal drug misuse in pregnancy may have adverse effects on infant visual and/or developmental outcome, but to date this has not been quantified. We have previously described abnormal visual evoked potentials (VEPs) in newborn infants exposed to methadone and other drugs of abuse in utero: We now describe visual and developmental outcomes at 6 months of age in a larger cohort of infants born to drug-misusing mothers. Methods: 100 term infants born to drug-misusing mothers prescribed substitute methadone in pregnancy and 50 control infants matched for birth weight, gestation and socio-economic group were recruited in the neonatal period. In utero drug exposure was determined by maternal history, maternal and infant urine and meconium toxicology. Infants underwent clinical visual evaluation at 6 months of age in conjunction with pattern-onset VEPs (to 15, 60 and 120 min of arc black and white checks) and Griffith's developmental assessment. Results: Retention rate of the maternal methadone-exposed cohort was 79%. The majority of infants were exposed to illicit drugs in addition to methadone including opiates (75%) and benzodiazepines (67%). Age at assessment (median 27 weeks, range 26–30), weight and OFC did not differ between groups. 40% of the maternal methadone-exposed cohort demonstrated one or more significant abnormalities on clinical visual assessment including nystagmus (11%), strabismus (25%) and reduced visual acuity (22%). Electrophysiological abnormalities persisted at 6 months of age: methadone-exposed infants had smaller amplitude pattern VEPs (25 μV vs 34 μV; p=0.005) with delayed peak latencies (115 ms vs 99 ms; p=0.019) and fewer responses at the small check size (p=0.003), compared to controls. Median GQ score in maternal methadone-exposed infants was 97 versus 105 for controls (p<0.001). Most infants scoring <85 on developmental assessment had co-existing visual problems. Conclusions: There is a high incidence of visual abnormalities in infants exposed to methadone and other drugs of misuse in utero. Persistence of electrophysiological abnormalities beyond the neonatal period suggests that opiates may have a teratogenic effect on the developing visual system. Early visual screening is warranted for infants born to drug-misusing mothers.